Модернізація вищої школи України в умовах інтеграції в європейський освітній простір - Пінчук, Є. А. (НТУ "ХПІ", 2009)
The basic problems of the educational system of Ukraine are regarded in the article, the author considers the matters of constructing the new model of management of the national educational system, which correlates with innovative character of the modified system of education which meets requirements of the Boulogne principles
Keywords: Болонський процес; Сорбонська декларація; Велика хартія університетів; Лісабонська конвенція; система двохетапної вищої освіти; система кредитних одиниць; підвищення конкурентоспроможності системи вищої освіти; розширення мобільності; акредитація